MULTIMODAL TEXTS: ARE THEY TRULY HELPFUL FOR NARRATIVE TEXT COMPREHENSION? - Yunita Wardani; Esti Kurniasih (University of Muhammadiyah Malang, 2023)
Commonly, in EFL context, in Indonesia, students face challenges when attempting to comprehend the text's content with monotonous activities which can influence their interest and motivation. Multimodal text is one of instructional materials which are a combination of meaning-making activities that conveys information, including visual images, written language, and other semiotic modes. This study was used qualitative research data were collected through observation and students’ result of reading task. One English teacher and the 32 students also participated. The result showed that the teacher implemented multimodal texts for assisting the students to comprehend narrative reading text in four meetings and using different stories and modes. There were seven kinds of reading tasks that the students almost got the good score. Moreover, the students’ reading task results of summary were analyzed using ESL Composition Profile and it can be concluded that all groups wrote using their own words. In sums, the students could learn and comprehend narrative reading text easily and effectively by using multimodal texts. This study is expected to have a benefit for English teachers to consider to attempt and provide some interesting materials that are acceptable with the multimodal texts.